52.7k views
3 votes
2x-5=3x^2 find the root of X

1 Answer

2 votes

For this case we must solve the following quadratic equation:


3x ^ 2-2x + 5 = 0

Where:


a = 3\\b = -2\\c = 5

The roots are given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Substituting the values we have:


x = \frac {- (- 2) \pm \sqrt {(- 2) ^ 2-4 (3) (5)}} {2 (3)}\\x = \frac {- (- 2) \pm \sqrt {(- 2) ^ 2-4 (3) (5)}} {2 (3)}\\x = \frac {2 \pm \sqrt {4-60}} {6}\\x = \frac {2 \pm \sqrt {-56}} {6}

By definition we have to:


i ^ 2 = -1\\x = \frac {2 \pm \sqrt {56i ^ 2}} {6}\\x = \frac {2 \pm i \sqrt {56}} {6}\\x = \frac {2 \pm i \sqrt {2 ^ 2 * 14}} {6}\\x = \frac {2 \pm 2i \sqrt {14}} {6}\\x = \frac {1 \pm i \sqrt {14}} {3}

We have two complex roots:


x_ {1} = \frac {1+ i \sqrt {14}} {3}\\x_ {2} = \frac {1- i \sqrt {14}} {3}

Answer:


x_ {1} = \frac {1+ i \sqrt {14}} {3}\\x_ {2} = \frac {1- i \sqrt {14}} {3}

User Rick Mangi
by
5.9k points